ENGLISH LANGUAGE MODULE FOR VOCATIONAL COLLEGE STUDENTS AND HOTEL STAFFS - Nawangsih Edynna Putri; Makmun Syaifudin (International Journal of Social Science, 2024)
Issue being raised in this study was a concern for the needs of compiling an English course book for hotel and hospitality students and hotel staffs at general. This is a mentorship activity focusing on helping research participants in compiling module for hotel staff and the general public who want to improve their English communication skills at the operational level in the hospitality industry. The research team consists of three lecturers from the hospitality study program and 41 students of vocational college (D3) taking hotel and hospitality study program in their 6th semester. The research mentoring activities were done in three stages: preparation, implementation, and assessment and was conducted from February to April 2024. The product analysis on the English language module for hospitality study program developed by the researcher after having assessed by reliable experts decided to be highly feasible, which means the e-Module development could be used for either students of hotel and hospitality or hotel staff at general. The practicality analysis was obtained from questionnaire declaring that the module was very practical. The analysis of the effectiveness of the e-Module was highly effective to be a reference book for students taking hotel and hospitality study program